Pelaksanaan Analisa Jabatan Pada Universitas Islam Kadiri - Endah Kurniawati (Universitas Islam Kadiri, 2018)
Job Analysis is a collection of data or information that concerns about the job/position to assign jobs description and requirement of job or position. With the job analysis of making a description of the job and position specifications. Information about the job that is in the document will be used in recruitment and selection, training and orientation, development, career management, organization management, and legal protection. The need for cooperation from some Office holders, the suitability of the data and the name of the position in the human resources section with the data in the related agencies. The need for personnel in the Organization's commitment to supporting the smooth execution of the analysis.